Gestational diabetes and risk of perinatal depression in low- and middle-income countries: a meta-analysis - Jin, Yuqing; Wu, Chengkai; Chen, Wanlin; Li, Jingsong; Jiang, Haiteng (Frontiers in Psychiatry, 2024)
The relationship between gestational diabetes (GDM) and the risk of depression has been thoroughly investigated in high-income countries on their financial basis, while it is largely unexplored in low-and middle-income countries. This meta-analysis aims to assess how GDM influences the risk of perinatal depression by searching multiple electronic databases for studies measuring the odds ratios between them in low-and middle-income countries. The risk of bias was assessed by two independent reviewers with a checklist. Although we searched for a range of mental disorders in electronic databases initially and found 16 observational studies met the inclusion criteria in total, only the number of studies on depression (n=10) satisfied the conditions to conduct a meta-analysis, showing the relationship between mental illness and GDM has been overlooked in low-and middle-income countries. Pooled odds ratios (ORs) and confidence intervals (CIs) were calculated using the random effect model. Evidence shows an elevated risk of perinatal depression in women with GDM (pooled OR 1.92; 95% CI 1.24, 2.97; 10 studies). Subgroup analyses were further conducted based on the type of study design and country income level. The increased risk of perinatal depression in patients with GDM was not significantly different between cross-sectional and prospective design. Moreover, we found that country income level is a significant factor that adversely influences the risk of perinatal depression in GDM patients. Our findings suggested that women with GDM are vulnerable to perinatal depressive symptoms, and a deeper understanding of potential risk factors and mechanisms may help inform strategies aimed at prevention of exposure to these complications during pregnancy.